Dual biologic therapy in inflammatory bowel disease, a retrospective cohort study of vedolizumab and anti‐tumor necrosis factor alpha therapy in children - Jonathan E. M. O'Donnell; Carlie Bolles; Claire R. Reilly; Manal Morgan; Christopher Burgess; Fariha Balouch; Peter J. Lewindon (Journal of Pediatric Gastroenterology and Nutrition, 2026)
Abstract Objectives Despite advances in pediatric inflammatory bowel disease (PIBD) with biologics, remission rates remain at 47%–60% with loss‐of‐response rates at 60%–68%. Evidence for efficacy of dual biologic therapy (DBT) with anti‐tumor necrosis factor alpha therapy (anti‐TNF‐α)‐ vedolizumab (VDZ) for children refractory to anti‐TNF‐α therapy is limited. This study aimed to describe rates of steroid‐free clinical remission (CR), endoscopic and histological remission, trends in biochemistry, predictors of response, and adverse events in this population. Methods We performed a retrospective study of children with PIBD treated with anti‐TNF‐α–VDZ DBT for 6–12 months from 2020 to 2023. Results Twenty‐two treatment episodes were analyzed in 21 patients (17 Crohn's disease, 5 ulcerative colitis) with 13 continuing to 12 months. CR increased from 9% at baseline to 68% at 3 months (95% confidence interval [CI] 47%–83%, p < 0.01), 55% at 6 months (95% CI 35%–73%, p < 0.05) and 50% at 12 months (95% CI 31%–69%, p < 0.05). Seventy‐two percent in total achieved CR during follow‐up. Endoscopic remission increased from 5% to 38% ( p = 0.02), histological remission from 5% to 29% ( p = 0.046). Fecal calprotectin decreased from 930 to 500 μg/g at 3 months ( p = 0.04), 680 μg/g at 6 months ( p = 0.03), and 255 μg/g at 12 months ( p = 0.12). Trends toward remission were observed in patients with colonic disease, incomplete response rather than loss of response to anti‐TNF‐α, and ulcerative colitis. Two significant adverse events occurred: pulmonary mucormycosis and herpes‐simplex virus keratitis. Conclusion Anti‐TNF‐α–VDZ DBT improved clinical, endoscopic, and histological outcomes in children refractory to biologic monotherapy. Lay Summary This study looked at children with inflammatory bowel disease who did not get better with one biologic. Using two biologic medicines together helped many children feel better, heal the gut lining, although some still needed surgery. Few had side effects.